1997
DOI: 10.1103/physreve.56.5717
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of collisional properties of spheres using high-speed video analysis

Abstract: In this paper we report measurements of collisional properties of spheres using high-speed video analysis. These results agree with a simple collision operator. We study the size and velocity dependences of the coefficient of restitution in the normal direction. The experimental data are compared with the relevant models of energy dissipation and show the existence of two dissipation regimes. For large impact velocities a plastic deformation model is in good agreement with our measurements, while for smaller v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 31 publications
11
114
0
Order By: Relevance
“…When the impact velocity v is large (v 5 m/s [10]), the colliding particles deform fully plastically and r ∝ v −1/4 , as reported experimentally [11,12,13,14] and theoretically [10,12,15,16]. When v 0.1 m/s [10], the deformations are elastic with mainly viscoelastic dissipation, and 1 − r ∝ v 1/5 , as reported experimentally [14,17,18] and theoretically [17,19]. Such velocity-dependent restitution coefficient models have recently shown to be important in numerical [20,21,22,23,24,25,26] and experimental [18,27] studies.…”
Section: The Variable Coefficient Of Restitutionmentioning
confidence: 90%
See 1 more Smart Citation
“…When the impact velocity v is large (v 5 m/s [10]), the colliding particles deform fully plastically and r ∝ v −1/4 , as reported experimentally [11,12,13,14] and theoretically [10,12,15,16]. When v 0.1 m/s [10], the deformations are elastic with mainly viscoelastic dissipation, and 1 − r ∝ v 1/5 , as reported experimentally [14,17,18] and theoretically [17,19]. Such velocity-dependent restitution coefficient models have recently shown to be important in numerical [20,21,22,23,24,25,26] and experimental [18,27] studies.…”
Section: The Variable Coefficient Of Restitutionmentioning
confidence: 90%
“…For more informations on restitution coefficient measurements, see Ref. [11,12,13,14,17,18,27,28,29].…”
Section: The Variable Coefficient Of Restitutionmentioning
confidence: 99%
“…For the particle-particle impact experiments, in contrast to the above category of devices, two particles collide without any rigid tool according to (Fig. 8b) [15,20,55,59]. This type of stressing occurs in fluidized bed granulation and comminution.…”
Section: Measurement Of the Restitution Coefficient Of A Granulementioning
confidence: 99%
“…7b. For elastic-plastic behaviour during the impact, the restitution coefficient is in the range of 0 < e < 1, see examples in [5,15,16,20,23,28,34,55,59,60,71,76,83,85,88,91,92].…”
Section: Measurement Of the Restitution Coefficient Of A Granulementioning
confidence: 99%
“…Several analytical and semi-empirical models have been developed to evaluate µ and e w in terms of flow parameters such as the impact velocity, impact angle, particle spin and the particle and wall properties [25][26][27][28][29]. While it has been shown that the frictional coefficient significantly affects the collision regime (sliding/non-sliding) [25], fluidization predictions are not sensitive to e w in the range 0.7-1.0 [1,30].…”
Section: Introductionmentioning
confidence: 99%